2014
DOI: 10.1186/gb-2014-15-3-r52
|View full text |Cite
|
Sign up to set email alerts
|

Genomic occupancy of Runx2 with global expression profiling identifies a novel dimension to control of osteoblastogenesis

Abstract: BackgroundOsteogenesis is a highly regulated developmental process and continues during the turnover and repair of mature bone. Runx2, the master regulator of osteoblastogenesis, directs a transcriptional program essential for bone formation through genetic and epigenetic mechanisms. While individual Runx2 gene targets have been identified, further insights into the broad spectrum of Runx2 functions required for osteogenesis are needed.ResultsBy performing genome-wide characterization of Runx2 binding at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
150
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 69 publications
10
150
0
2
Order By: Relevance
“…Our finding that EZH2 attenuates osteoblastogenesis is relevant to skeletal deformities seen in congenital human disorders and consistent with accruing data on epigenetic regulation of osteoblast differentiation (22,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)59). Our initial studies with mice lacking functional Ezh2 expression in mesenchymal progenitor cells show premature closure of the cranial sutures characteristic of craniosynostosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that EZH2 attenuates osteoblastogenesis is relevant to skeletal deformities seen in congenital human disorders and consistent with accruing data on epigenetic regulation of osteoblast differentiation (22,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)59). Our initial studies with mice lacking functional Ezh2 expression in mesenchymal progenitor cells show premature closure of the cranial sutures characteristic of craniosynostosis.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a recent study has demonstrated that suppression of Ezh2 expression is potentially controlled by up-regulation of Runx2 in mature osteoblasts (59). Furthermore, the long noncoding RNA LncRNA-ANCR targets EZH2, and this inhibition of EZH2 supports expression of RUNX2 (60).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic marks in osteoblastic cells (15,16,21) and in adipocyte cell culture models (22) have revealed distinct patterns for gene expression in terminally differentiated cell types. Previous research has determined that the histone-modifying enzymes responsible for many of these patterns, including KDM5B, EZH2, and others, play a clear role in skeletal development and differentiation of the MSC through modulation of RUNX2 (23,24).…”
mentioning
confidence: 99%
“…While these areas are often responsible for controlling gene expression [34], many other potential regions of gene expression control exist. Nonpromoter regions such as upstream regions (À1 to À20 kb from transcription start site), introns, exons, and intergenic regions have been demonstrated to bind Runx2 during osteogenic differentiation [35]. Finally, we were limited to evaluating a few target genes, but many more genes are expressed during the course of osteogenic and adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%